Prinsip Kepemimpinan Moral Spiritual Sekolah Dalam Pembangunan Karakter PAUD di TK Nurul Hidayah Kabupaten Serdang Bedagai: Principles of School Spiritual Moral Leadership in PAUD Character Building in Kindergarten Nurul Hidayah, Serdang Bedagai District - Hotni Sari Harahap; Armanila Armanila (Universitas Ngudi Waluyo, 2023)
Early childhood education is a fundamental educational process. Children at an early age will find it very easy to imitate or imitate what they see so that with the ability of the principal to display leadership that emphasizes the moral-spiritual aspect, it will be able to help early childhood in shaping their character. This study aims to find out how spiritual-moral-based principal leadership can improve character learning. The research method uses a descriptive qualitative approach. The results of the study show that through a moral-spiritual leadership approach there are three stages in the formation of character, namely moral knowing; moral feeling; and moral action is easier to implement through the learning process. As input material for school principals, they should choose a moral-spiritual leadership approach in forming character, namely moral knowing; moral feeling; and moral action is easier to implement through the learning process. The selection of the right spiritual-moral leadership approach can influence the formation of the character of student achievement. ABSTRAK Pendidikan anak usia dini merupakan proses pendidikan yang fundamental. Anak di usia dini akan sangat mudah dalam meniru atau mencontoh apa saja yang dilihatnya sehingga dengan kemampuan kepala sekolah menampilkan kepemimpinan yang menonjolkan pada aspek moral spiritual akan mampu membantu anak usia dini dalam membentuk karakternya. Penelitian ini bertujuan untuk mengetahui bagaimana kepemimpinan kepala sekolah berbasis moral spiritual mampu meningkatkan pembelajaran karakter. Metode penelitian menggunakan pendekatan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa melalui pendekatan kepemimpinan moral spiritual tiga tahapan dalam pembentukan karaktek yakni moral knowing; moral feeling; dan moral action lebih mudah diimplementasikan melalui proses pembelajaran. Sebagai bahan masukan bagi kepala sekolah sebaiknya memilih pendekatan kepemimpinan moral spiritual dalam pembentukan karaktek yakni moral knowing; moral feeling; dan moral action lebih mudah diimplementasikan melalui proses pembelajaran. Pemilihan pendekatan kepemimpinan moral spiritual yang tepat dapat berpengaruh terhadap dalam pembentukan karaktek pencapaian prestasi belajar siswa.